2002
DOI: 10.1080/0028825x.2002.9512810
|View full text |Cite
|
Sign up to set email alerts
|

Screening of 50 Cunoniaceae species from New Caledonia for antimicrobial properties

Abstract: Some species of the Cunoniaceae are reputed to possess medicinal properties. An investigation of 50 species of this family in New Caledonia has permitted the screening of 204 extracts (101 ethyl acetate extracts and 103 methanol extracts) for antimicrobial activities against one yeast (Candida albicans), one filamentous fungus (Fusarium oxysporum), and eight bacterial species (Erwinia carotovora, Klebsiella pneumoniae, Pseudomonas aeruginosa, Escherichia coli, Staphylococcus aureus, Staphylococcus epidermidis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Since previous studies on crude methanolic extract of C. macrophylla leaves showed antibiotic activities (Fogliani et al, 2002a), we decided to extract leaves using a Soxhlet apparatus with three solvents (dichloromethane, ethyl acetate, methanol) to separate bioactive molecules. The results clearly showed that activities were concentrated in the methanolic extract (89.4 g) (Fig.…”
Section: Bioactivity Guided Separationmentioning
confidence: 99%
See 1 more Smart Citation
“…Since previous studies on crude methanolic extract of C. macrophylla leaves showed antibiotic activities (Fogliani et al, 2002a), we decided to extract leaves using a Soxhlet apparatus with three solvents (dichloromethane, ethyl acetate, methanol) to separate bioactive molecules. The results clearly showed that activities were concentrated in the methanolic extract (89.4 g) (Fig.…”
Section: Bioactivity Guided Separationmentioning
confidence: 99%
“…Our screening of 50 species of Cunoniaceae from New Caledonia for antimicrobial properties (Fogliani et al, 2002a) and for inhibitors of xanthine oxidase and scavengers of superoxide anions (Fogliani et al, 2002b) have revealed bioactive potential of some species. Cunonia macrophylla Brongniart & Gris in particular showed a capacity to inhibit bacteria as well as fungi.…”
Section: Introductionmentioning
confidence: 99%
“…This species displays good resistance to drought in its natural environment, and is common on serpentine at low altitudes. Biomolecules of pharmacological interest have been identified in this species (Fogliani et al, 2002a(Fogliani et al, , 2002b. Some other Cunonlaceae in New Caledonia belonging to the genera Geissois and Pancheria accumulate aluminum (Al) and Ni (Jaffré et al, 1979).…”
Section: Introductionmentioning
confidence: 98%
“…The crude plant extract was obtained using the organic solvent ethanol immersion method modified from a previous study [15]. The air-dried plant was ground into a powder with a shredder.…”
Section: Collection and Preparation Of Plant-derived Extractsmentioning
confidence: 99%
“…Plant resources are extraordinarily rich in China, with more than 10,000 kinds of Chinese herbal medicine resources, 1,400 kinds of plants with inhibitory activity, and 4,000,000 kinds of secondary metabolites [13]. Fogliani studied the antibacterial activity of 50 species of fire-barrel tree plants from Scotland and reported that 49 inhibited spores to varying extents [15]. Ojala et al showed that extracts of wrinkled parsley and fennel have antibacterial effects on antiseptic sclerosis [16].…”
Section: Introductionmentioning
confidence: 99%